Mental motivation and its relationship with skilled self of handball for students - Mohisen Abdul Ameer, Firas; Ali Slumy, Amel; Mohammed Hamzha, Salam (International Journal of Psychosocial Rehabilitation, 2020)
The importance of identifying the mental motivation and its relationship to the skilled self in handball for students, with reference to the scarcity of studies on these variables among students of the faculties of physical education and sports sciences of some universities of the Middle Euphrates, according to the researchers’ knowledge. As for the research problem, it is mental motivation is one of the modern and old concepts at the same time, it is old, if it is dealt with as a tendency aspect of thinking (the concept of the tendency to think) and under different names such as desire, tendency, willingness or desire to think, and the concept of mental motivation can be considered a modern concept from on the one hand, the results of brain research, its operations, and the care of thinking patterns in the brain emerged, while the skilled self is the awareness of the state’s level of basic skills and continuing to perform exercises on it in a high spirit, through the perception of the attractiveness of the body formation and the ability to maintain the body and confidence in the outward appearance of the body, and the perception of skill capacity and muscle growth and confidence in situations that require the use of ability, and awareness of the level of the state or mobility, the ability to continue performing exercises for a relatively long period and self-confidence when practicing basic skills exercises, and the awareness of sport ability, the ability to learn motor skills and self-confidence in sports situations. Handball is one of the group sports that need speed, decision-making, and consensus with colleagues, whether during the lesson, exercise, or play, and mastering and learning the game of handball requires practice, training, and knowledge of everything related to this game, whether in terms of skills or law, in addition to continuous follow-up on attendance and commitment to the lessons of this game. Believing from researchers in the importance of mental motivation among students in their academic career in general, as well as the skilled self that has a role in learning and self-confidence in sports situations, which prompted researchers to study these variables and stand on their true reality by studying mental motivation and its relationship to the skill self of college students in physical education and sports science in some universities of the Middle Euphrates, it is a modest scientific endeavor to contribute to his service to his community. And that the research objectives are: identifying the reality of mental motivation and the skill of hand reeling for fourth-stage students in the College of Physical Education and Sports Sciences of some universities of the Middle Euphrates (Babylon, Karbala, and Qadisiyah) for the academic year (2019-2020) and identifying the relationship between mental motivation and the skill of hand reeling for fourth-year students in the College of Physical Education and Sports Sciences of some universities of the Middle Euphrates (Babylon, Karbala, and Qadisiyah) for the academic year (2019-2020). The researchers also hypothesized: There is a correlation between both mental motivation and the skilled self of handball for fourth-year students in the college of physical education and sports sciences of some universities of the Middle Euphrates (Babylon, Karbala, and Qadisiyah) for the academic year (2019-2020). The researchers used the descriptive approach of the two methods, survey studies and correlational relations, in order to suit them to the research requirements. The research community included students of the fourth stage of the faculties of physical education and sports sciences of some Middle Euphrates universities (Babylon, Karbala, and Qadisiyah) for the academic year (2019-2020), and their number was 404 students. They were distributed over the University of Babylon (142 students), the University of Karbala (110 students), and the University of Qadisiyah (152 students). While the application sample consisted of 120 students, and they were chosen by a simple random method, the results were extracted statistically by using SPSS to extract the results. Consequently, the results were presented and discussed in chapter four, and the researchers reached conclusions and recommendations, and the most important conclusions were that the members of the research sample enjoyed good amounts of all mental motivation and skilled self in handball, and there was a significant correlation between mental motivation and the skilled self of handball for fourth-stage students in the college of physical education and sports sciences in some Iraqi universities. The researchers also recommended the need to move towards building educational-training programs that contribute to building mental motivation among students of the fourth stage in the college of physical education and sports sciences in Iraqi universities, the need to move towards building educational-training programs for self-skilled students, and the need for the teacher’s attention in addition to psychological preparation for students in order to control the level of mental motivation and self-skill and make it a good level.